The Observers Observed: 'Reflections on making a film, The Day War Broke Out, with the Mass Observation Archive' by three PhD researchers - Elizabeth Chappell; Simon King; Dominique Baron-Bonarjee (Janeway JS, 2021)
Elizabeth Chappell, Simon King and Dominique Baron-Bonarjee made a film, The Day War Broke Out, in the summer of 2019 as part of a CHASE film making training course led by film-maker Karen Boswall at The University of Sussex. The film focuses on the way in which the Mass Observation (MO) Archive came about. The film brings to life the materiality of the archive through voice, music, hand-written letters, historical objects and setting as well as through an interview with one of Mass Observation’s curators, Kirsty Pattrick. But what can we understand from the stated intentions of MO’s founders for anonymous volunteer contributors to write diaries ‘so that their [the public’s] environment may be understood and thus constantly transformed.’? This article takes the view that the ‘single voice’, i.e. in this case the personal reflective narrative, can offer a ‘way in’ to understanding collective lived experience. Exploring the research questions through three case studies, it offers a dialogical approach to the parallel and overlapping questions of how past lived experience can be brought to life on film as well as how researchers can use materiality to access the context of lived experience. It asks, how does the creative exploration of the archive through film offer the possibility of a more open dialogue to occur between researchers and curators? And finally, how can film making open up new vistas and avenues for researchers to share findings as well as to transform their own field of research?